Intra-session and inter-rater reliability of spatial frequency analysis methods in skeletal muscle - Crawford, Scott K.; Lee, Kenneth S.; Bashford, Greg R.; Heiderscheit, Bryan C. (PLOS ONE, 2020)
Spatial frequency analysis (SFA) is a quantitative ultrasound (US) method originally developed to assess intratendinous tissue structure. This method may also be advantageous in assessing other musculoskeletal tissues. Although SFA has been shown to be a reliable assessment strategy in tendon tissue, its reliability in muscle has not been investigated. The purpose of this study was to examine the reliability of spatial frequency parameter measurement for a large muscle group within a healthy population. Ten participants with no history of lower extremity surgery or hamstring strain injury volunteered. Longitudinal B-mode images were collected in three different locations across the hamstring muscles. Following a short rest, the entire imaging procedure was repeated. B-mode images were processed by manually drawing a region of interest (ROI) about the entire muscle thickness. Four spatial frequency parameters of interest were extracted from the image ROIs. Intra- and inter-rater reliabilities of extracted SFA parameters were performed. Test-retest reliability of the image acquisition procedure was assessed between repeat trials. Intraclass correlation coefficients showed high intra- and inter-rater reliability (ICC(3,1) > 0.9 for all parameters) and good to moderate test-retest reliability (ICC(3,1) > 0.50) between trials. No differences in parameter values were observed between trials across all muscles and locations (p > 0.05). The high reliability metrics suggest that SFA will be useful for future studies assessing muscle tissue structure, and may have value in assessing muscular adaptations following injury and during recovery.